Entrapped in Olive-Harvesting Nets: A Case of a Grass Snake Natrix natrix from an Olive-Growing Greek Aegean Island - Yiannis G. Zevgolis; Apostolos Christopoulos (Diversity, 2023)
Despite a recent shift towards sustainable practices to support the conservation of traditional olive groves, little is known about their potential threats to herpetofauna species. On the island of Lesvos, one of the main olive-growing islands in the Mediterranean, olive cultivation often prioritizes the expeditious harvesting of olives with minimal or no supplementary intervention, resulting in their generally suboptimal management, a component of which also pertains to the olive nets that, in many cases, remain dispersed and unfurled throughout the groves. This particular practice affects the species living in the olive groves, making them more prone to risks related to their accidental trapping. In this study, we report the first case of a Grass snake being inadvertently trapped in an olive net laid out on an olive grove. The position of the snake under the net, within a folded tipping, made it difficult for it to escape, and it became increasingly entangled. Based on this incident, it is plausible to assume that similar cases may occur in areas where nets are used in olive groves, both in Greece and other olive-growing countries. Further systematic research is necessary to determine the extent of this issue.